Unstable control of breathing can lead to ineffective noninvasive ventilation in amyotrophic lateral sclerosis. Issue 3 (22nd July 2019) - Sancho, Jesús; Burés, Enric; Ferrer, Santos; Ferrando, Ana; Bañuls, Pilar; Servera, Emilio
Upper airway obstruction with decreased central drive (ODCD) is one of the causes of ineffective noninvasive ventilation (NIV) in amyotrophic lateral sclerosis (ALS). The aim of this study is to determine the mechanism responsible for ODCD in ALS patients using NIV. This is a prospective study that included ALS patients with home NIV. Severity of bulbar dysfunction was assessed with the Norris scale bulbar subscore; data on upper or lower bulbar motor neuron predominant dysfunction on physical examination were collected. Polysomnography was performed on every patient while using NIV and the ODCD index (ODCDI: number of ODCD events/total sleep time) was calculated. To determine the possible central origin of ODCD, controller gain was measured by inducing a hypocapnic hyperventilation apnoea. Sonography of the upper airway during NIV was performed to determine the location of the ODCD. 30 patients were enrolled; three (10%) had ODCDI >5 h −1 . The vast majority of ODCD events were produced during non-rapid eye movement sleep stages and were a consequence of an adduction of the vocal folds. Patients with ODCDI >5 h −1 had upper motor neuron predominant dysfunction at the bulbar level, and had greater controller gain (1.97±0.33 versus 0.91±0.36 L·min −1 ·mmHg −1 ; p<0.001) and lower carbon dioxide (CO2 ) reserve (4.00±0.00 versus 10.37±5.13 mmHg; p=0.043). ODCDI was correlated with the severity of bulbar dysfunction (r= −0.37; p=0.044), controller gain (r=0.59; p=0.001) and CO2 reserve (r= −0.35; p=0.037). ODCD events in ALS patients using NIV have a central origin, and are associated with instability in the control of breathing and an upper motor neuron predominant dysfunction at the bulbar level. Upper airway obstructions in ALS patients using NIV have a central origin, and are associated with instability in the control of breathing and an upper motor neuron predominant dysfunction at the bulbar level http://bit.ly/2WEMt28